2004
DOI: 10.1002/chem.200305427
|View full text |Cite
|
Sign up to set email alerts
|

Steric and Electronic Effects in Cyclic Alkoxyamines—Synthesis and Applications as Regulators for Controlled/Living Radical Polymerization

Abstract: The synthesis of new six- and seven-membered cyclic alkoxyamines bearing ethyl groups at the alpha-N position of the alkoxyamines is described. The key step in the synthesis of the sterically hindered six-membered cyclic alkoxyamines is a Wadsworth-Horner-Emmons olefination with bisphosphonate 1. The seven-membered cyclic alkoxyamines were prepared from the corresponding six-membered keto alkoxyamines by ring-enlargement with trimethylsilyl(TMS)-diazomethane. The use of the new alkoxyamines as regulators/initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 39 publications
7
93
0
4
Order By: Relevance
“…Alkoxy amine 5, which has a sterically more demanding nitroxide moiety, [16] was prepared in an analogous manner (see the Supporting Information). Compound 4 forms stable monolayers in a mixture with DPPC at the air/water interface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkoxy amine 5, which has a sterically more demanding nitroxide moiety, [16] was prepared in an analogous manner (see the Supporting Information). Compound 4 forms stable monolayers in a mixture with DPPC at the air/water interface.…”
Section: Methodsmentioning
confidence: 99%
“…Alkoxy amine 5 bears a nitroxide group, which is able to control acrylate polymerization. [16] LB lithography was performed with a mixed DPPC/5 monolayer containing 10 mol % 5. The regularity of stripe pattern improved significantly, indicating better compatibility of 5 with DPPC.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lipophilicity of the ibuprophen-nitroxides, nitroxide-radicals in compounds 2-5 were no detectable in PBS. Log P o/w of 1 was also 3 ) for 200-Folds Excess AsA The rates of reduction for nitroxides 1-5 were studied under pseudo-first-order conditions using a 200-fold excess of AsA in DMSO. Second-order rate constants, k were obtained by monitoring the decay of the low-field EPR peak height of nitroxides/peak height of the Mn marker from 2 min to 10 min after reaction at 295 K (Fig.…”
Section: H-nmr and Epr Spectra Of 1-6mentioning
confidence: 99%
“…They had different reduction rates for reductants such as ascorbic acid (AsA), and these were applied as an invivo probe. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The rate constant of reduction of a nitroxide probe in vitro is expected to be a guideline of its half-life in vivo. [9][10][11] The rate constants of them are greatly different and could not measure under the same conditions.…”
mentioning
confidence: 99%
“…For example, Yoshioka et al reported on the synthesis for piperidine nitroxides having a spirocyclohexyl group via , -unsaturated ketone derivatives (Yoshioka et al, 1972). In addition, focusing on substitution of the tetraethyl group, Studer et al reported a stepwise synthesis via bisphosphonates (Wetter et al, 2004), and also -lactams for obtaining piperidine nitroxides on a large scale (Schulte et al, 2005) which involved several synthetic steps and a high-pressure reactor.…”
Section: Piperidinementioning
confidence: 99%